Anesthesia For Laparoscopic Cholecystectomy In A Patient With Transverse Myelitis: A Case Report - Sharma, Achyut; Khatiwoda, Shikshya; Khanal, Kishor; Sharma, Apurb; Bhattarai, Prajjwal Raj (Nepal Mediciti Medical Journal, 2021)
Background: Transverse Myelitis is a rare inflammatory disorder of the spinal cord presenting with sensory, motor, and autonomic dysfunction. Patients of transverse myelitis may present to operation theater for a variety of surgical procedures. The debilitating nature of the disease and interaction with anesthetic agents poses serious challenges during perioperative period. Choice of anesthesia is debatable but the complication following anesthesia can be prevented with thorough preoperative preparation and judicious use of anesthetic agent with neuromuscular monitoring. We present a successful conduction of laparoscopic cholecystectomy in a patient with transverse myelitis. Case Presentation: A 55-year-old female who was a known case of transverse myelitis presented for laparoscopic cholecystectomy to remove a gall bladder polyp. Except for weakness in bilateral lower limbs which had improved since her diagnosis of transverse myelitis two months back, she had no significant past medical and surgical history. Considering the grave possibility of malignant potential in polyp, cholecystectomy was urgent. Her vitals were within normal limits. Other systemic examinations revealed no abnormalities. She was planned under general anesthesia with avoidance of muscle relaxants and intraoperative use of bispectral index and train-of-four monitoring. The intra-operative period was successfully managed with propofol induction, fentanyl as analgesia, I-gel for maintenance of airway, and isoflurane for maintenance of anesthesia. Bispectral index was targeted to 40-60. Intra-operative, and post-operative period was uneventful and she had no exacerbation in her symptoms in the subsequent follow-up. Conclusion: As transverse myelitis is an uncommon condition and often not encountered routinely, the patient present real anesthetic challenge for an unsuspecting anesthesiologist. The successful management of such case especially with the use of novel anesthetic monitoring technique provide us with sufficient evidence that dreadful complications of transverse myelitis like exacerbation of motor, sensory and autonomic dysfunction can be avoided.